Tnfrsf12a-Mediated Atherosclerosis Signaling and Inflammatory Response as a Common Protection Mechanism of Shuxuening Injection Against Both Myocardial and Cerebral Ischemia-Reperfusion Injuries - Lyu, Ming; Cui, Ying; Zhao, Tiechan; Ning, Zhaochen; Ren, Jie; Jin, Xingpiao; Fan, Guanwei; Zhu, Yan (Frontiers in Pharmacology, 2018)
Shuxuening injection (SXNI) is a widely prescribed herbal medicine of Ginkgo biloba extract (EGB) for cerebral and cardiovascular diseases in China. However, its curative effects on ischemic stroke and heart diseases and the underlying mechanisms remain unknown. Taking an integrated approach of RNA-seq and network pharmacology analysis, we compared transcriptome profiles of brain and heart ischemia reperfusion injury in C57BL/6J mice to identify common and differential target genes by SXNI. Models for myocardial ischemia reperfusion injury (MIRI) by ligating left anterior descending coronary artery (LAD) for 30 min ischemia and 24 h reperfusion and cerebral ischemia reperfusion injury (CIRI) by middle cerebral artery occlusion (MCAO) for 90 min ischemia and 24 h reperfusion were employed to identify the common mechanisms of SXNI on both cerebral and myocardial ischemia reperfusion. In the CIRI model, ischemic infarct volume was markedly decreased after pre-treatment with SXNI at 0.5 mL/kg, 2.5 mL/kg and 12.5 mL/kg. In the MIRI model, pre-treatment with SXNI at 2.5 mL/kg and 12.5 mL/kg improved cardiac function and coronary blood flow and decreased myocardial infarction area. Besides, SXNI at 2.5 mL/kg also markedly reduced the levels of LDH, AST, CK-MB and CK in serum. RNA-seq analysis identified 329 differentially expressed genes (DEGs) in brain and 94 DEGs in heart after SXNI treatment in CIRI or MIRI models, respectively. Core analysis by Ingenuity Pathway Analysis (IPA) revealed that atherosclerosis signaling and inflammatory response were top-ranked in the target profiles for both CIRI and MIRI after pre-treatment with SXNI. Specifically, Tnfrsf12a was recognized as an important common target, and was regulated by SXNI in CIRI and MIRI. In conclusion, our study showed that SXNI effectively protects brain and heart from I/R injuries via a common Tnfrsf12a-mediated pathway involving atherosclerosis signaling and inflammatory response. It provides a novel knowledge of active ingredients of Ginkgo biloba on cardio-cerebral vascular diseases in future clinical application.